Conversion of mouse fibroblasts into cardiomyocyte-like cells using small molecule treatments. (June 2015) - Park, Gyuman; Yoon, Byung Sun; Kim, Yoon Sik; Choi, Seung-Cheol; Moon, Jai-Hee; Kwon, Suhyun; Hwang, Jihye; Yun, Wonjin; Kim, Jong-Ho; Park, Chi-Yeon; Lim, Do-Sun; Kim, Yang In; et al.
Abstract: The possibility of controlling cell fates by overexpressing specific transcription factors has led to numerous studies in stem cell research. Small molecules can be used, instead of transcription factors, to induce the de-differentiation of somatic cells or to induce pluripotent cells (iPSCs). Here we reported that combinations of small molecules could convert mouse fibroblasts into cardiomyocyte-like cell without requiring transcription factor expression. Treatment with specific combinations of small molecules that are enhancer for iPSC induction converted mouse fibroblasts into spontaneously contracting, cardiac troponin T-positive, cardiomyocyte-like cells. We specifically identified five small molecules that can induce mouse fibroblasts to form these cardiomyocyte-like cells. These cells are similar to primary cardiomyocytes in terms of marker gene expression, epigenetic status of cardiac-specific genes, and subcellular structure. Our findings indicate that lineage conversion can be induced not only by transcription factors, but also by small molecules.